Herringbone structure in GeTe-based thermoelectric materials. (1st June 2015) - Lee, Ho Seong; Kim, Bong-Seo; Cho, Chang-Woo; Oh, Min-Wook; Min, Bok-Ki; Park, Su-Dong; Lee, Hee-Woong
Abstract: We investigated the microstructure of GeTe-based thermoelectric materials by using transmission electron microscopy. GeTe-based materials with a rhombohedral structure showed a herringbone structure, which is described as a regular arrangement of domain structures. The crystal region with different rhombohedral axis formed a domain. Domains with different variants showed alternative white and black contrast. We proposed a parallelepiped domain unit surrounded by (0 0 1), ( 1 1 ¯ 0 ) and ( 1 1 1 ¯ ) planes. Domain units were arranged along a specific direction 〈0 0 1〉 and 〈1 1 0〉, which formed many colonies. Well-aligned colonies comprised various kinds of herringbone structures. Several herringbone structures were described in detail based on the transmission electron microscopy results.